Implementing Community‐Based Participatory Research with Communities Affected by Humanitarian Crises: The Potential to Recalibrate Equity and Power in Vulnerable Contexts. Issue 3 (14th August 2020) - Afifi, Rima A.; Abdulrahim, Sawsan; Betancourt, Theresa; Btedinni, Dima; Berent, Jenna; Dellos, Laura; Farrar, Jordan; Nakkash, Rima; Osman, Rilwan; Saravanan, Monisa; Story, William. T.; Zombo, Moses; et al.
Abstract: Worldwide, over 70.8 million people are forcibly displaced from their homes as a result of persecution, conflict, violence, or human rights violation. In humanitarian crises, protection and the provision of basic needs are often prioritized. Research may be seen as opportunistic. However, without documenting and researching humanitarian responses, knowledge is not shared and does not accumulate, limiting the application of evidence‐based interventions where they are most needed. Research in humanitarian crises is complex, both ethically and methodologically. Community‐engaged research, and specifically community‐based participatory research (CBPR), can address some of the challenges of research in these settings. Using case studies of research we have conducted with communities affected by humanitarian crises, we highlight challenges and opportunities of the application of the ten core principles of CBPR in humanitarian settings. Despite some challenges and barriers, CBPR is a highly effective approach to use when engaging these populations in research. We argue that the application of CBPR in these settings has the potential to recalibrate the scales of equity and power among vulnerable populations. Highlights: Research in humanitarian crises is complex, both ethically and methodologically. Community‐based participatory research (CBPR) can address challenges of research in these settings. We describe application of CBPR principles in communities affected by protracted humanitarian crises. Choosing a CBPR approach with these communities can reverse power imbalance and recalibrate equity. Community psychology is uniquely placed to promote CBPR in these contexts.